Dynamic changes of neutralizing antibody and memory T cell responses six months post Omicron XBB reinfection - Zhao, Xin-Jing; Li, Xin-Lou; Zhang, Sheng; Chen, Jin-Jin; Zhao, Wei-Chao; Wu, Na-Na; Wang, Rui-Juan; Xu, Qiang; Lv, Chen-Long; Jiang, Bao-Gui; Wang, Guo-Lin; Fang, Li-Qun (Frontiers in Immunology, 2024)
Introduction: With the continued prevalence of COVID-19, repeated infection caused by SARS-CoV-2 has become common. However, studies on immune persistence post Omicron XBB reinfection are limited.We prospectively studied the durability and cross-reactivity of neutralizing antibodies (NAbs) and T cell responses among 20 subjects who suffered Omicron BA.5 infection with or without Omicron XBB reinfection over 6-month through the pseudovirus neutralization test and the fluorospot assay.Results: NAbs against EG.5.1, BA.2.86, and JN.1 subvariants were decreased and undetectable at 6-month post Omicron BA.5 infection, while those elicited by Omicron XBB reinfection were significant increased and remained detectable against all detected variants within 6-month. Furthermore, in subjects with Omicron XBB reinfection, memory T cell responses could cross-recognized wild-type and Omicron spike peptides and reached peak at 3-month. Interestingly, comparable robust T cell responses were observed among non-seroconverted subjects post Omicron XBB exposure.Though the NAbs against various emerging Omicron subvariants elicited by Omicron XBB reinfection can persist for at least 6-month, the HCWs should strengthen personal protection and timely be immunized with updated vaccines upon current circulating variants or conserved T epitope.